Employment of Bandrek Venders and Karo’s Traditional Medicine to Enhancement the Mutual and Production Marketing through Modernization of Equipment - Mauly Purba; Albiner Siagian; Evawany Y Aritonang (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The public's need for natural medicines that can be consumed practically urges processed spice traders to continue to improve the quality and quantity of products marketed. The problem with traders of bandrek and traditional ingredients is the lack of equipment that supports the quality of the ingredients used as basic ingredients for bandrek and traditional Karo ingredients. Equipment that is very important in this business is a machine for grinding basic ingredients to produce a finer composition of ingredients. Apart from that, the packaging for bandrek products and traditional ingredients is more hygienic and attractive to support the sales appeal and hygiene of the products produced. Based on the existing problems, community service activities provide the necessary equipment in the form of a finer spice grinding machine with a large grinding capacity. Apart from that, there were also 1000 pieces of packaging for bandrek with the LPPM USU logo. The aim of this service is to help traders of bandrek and traditional Karo medicine so that they can improve the quality and marketing of production by providing assistance with flouring tools/machines. The method of socializing product benefits and demonstrating the use of flouring machines is carried out directly to traders of bandrek and traditional Karo medicine. This activity has an impact on increasing traders' awareness to maintain the quality and marketing of bandrek production and Karo traditional medicine through equipment modernization, so that it can provide profits for traders